PELVIS GLOBAL TECHNIQUE FOR REDUCTION OF PAIN IN YOUTH WITH CHRONIC LOW BACK PAIN (Fiep Bulletin - online, 2016)
Introduction: Chronic low back pain is characterized by pain symptoms, which lasts for more than three months in the lumbar spine. It most often affects the people in their most productive period of life. Vertebral manipulation techniques are used in the treatment of back pain and aim to recover the physiological movement in areas where the restriction or dysfunction was installed. Objective: This study aims to investigate the relationship between chronic low back pain and lumbar manipulation. Methodology: an uncontrolled clinical trial, cross, qualitative and quantitative cutting was performed. The sample consisted of 15 individuals with chronic low back pain. An assessment was made of the whole: the sacrum, iliac, and lower lumbar pain, through the sitting flexion test, flexion standing, Mitchell and EVA to quantify pain; after the dysfunction observed was carried Global technical hip. Results: The study results showed a statistically significant decrease in the number of post-manipulation pain. Conclusion: We conclude, therefore, that for the present study, overall handling pelvis is effective in reducing low back pain symptoms and disorders in the alignment of the sacrum, iliac and lower lumbar spine.
Keywords: Global Technical pelvis. Chronic low back pain. Articular correction.